PENGARUH OPINI AUDIT SEBELUMNYA, PERUBAHAN MANAJEMEN, KEPEMILIKAN PUBLIK DAN REPUTASI AUDITOR TERHADAP AUDITOR SWITCHING - Mamolla Randy; Andreas Andreas; Ilham Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to examine and analyze the effect of previous audit opinion, management change, public ownership on auditor switching and auditor reputation on auditor switching. The population of this study were 18 real estate & property companies listed on the Indonesia Stock Exchange in 2014-2018. The type of data used is documentary data, namely research data in the form of financial reports that have been published from 2014-2018. The method of analysis used in this research is logistic regression analysis. The results showed that the audit opinion had no effect on auditor switching, which was evident from the significance value of 0.506> 0.05. Management change has no effect on auditor switching which is evident from a significance value of 0.695> 0.05. Public share ownership has no effect on auditor switching as evidenced by a significance value of 0.734> 0.05). Audit reputation has no effect on auditor switching which is evident from a significance value of 0.731> 0.05.Keywords: Previous Audit Opinion, Management Change, Public Ownership and Auditor Reputation Against Auditor Switching